2014
DOI: 10.2981/wlb.12065
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Human Disturbance on Capercaillie Tetrao urogallus Distribution and Demography in Scottish Woodland

Abstract: Leisure activities in fragmented western European forests are thought to threaten local populations of capercaillie Tetrao urogallus. We studied impacts of human disturbance on capercaillie in three Scottish woods by documenting the distribution of their droppings in relation to woodland tracks and entrances, surrogates for human activity. Droppings were sparser within 300-800 m of entrances and 70-235 m of tracks, depending on track use and habitat. Some 75% of each wood lay within 130 m of a track. In the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
36
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 61 publications
4
36
1
Order By: Relevance
“…Previous studies also found significant avoidance of recreational trails by capercaillie with distance‐thresholds ranging from 73 m (Summers et al ) up to 125 m (Moss et al ). The threshold values we determined were slightly higher, but in a similar order of magnitude, with mountain bike trails being avoided up to an average distance of 145 m and winter recreation infrastructure up to 320 m. This similarity – despite the studies were performed in different areas using different study methods – indicates that the results might apply to a wide geographical range for capercaillie.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Previous studies also found significant avoidance of recreational trails by capercaillie with distance‐thresholds ranging from 73 m (Summers et al ) up to 125 m (Moss et al ). The threshold values we determined were slightly higher, but in a similar order of magnitude, with mountain bike trails being avoided up to an average distance of 145 m and winter recreation infrastructure up to 320 m. This similarity – despite the studies were performed in different areas using different study methods – indicates that the results might apply to a wide geographical range for capercaillie.…”
Section: Discussionmentioning
confidence: 74%
“…Recreation activities have been shown to reduce woodland bird densities (van der Zande et al ), bird community composition and nest predation (Miller et al ) or breeding success (Anderson and Keith , Ahlund and Götmark ). Effects of this so called ‘anthropogenic disturbance’ – in this context defined as any form of human presence that triggers one of the above responses in wildlife – varies widely between species (Ficetola et al ), and can differ between sexes in the same species (Baydack and Hein , Moss et al ). Furthermore they strongly depend on the exact type of human activity or even the way humans behave during the same type of activity (Fernández‐Juricic et al ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Moss et al, 2014;Rösner et al, 2013;Thiel et al, 2011). Human disturbance may influence metapopulation dynamics and contribute to genetic impoverishment in small populations (Moss et al, 2014). For example, collisions with ski-lift cables may increase capercaillie mortality.…”
Section: Capercaillie and Tourismmentioning
confidence: 99%